The burden of iodine deficiency - Zhifei Wu; Yu Liu; Wenjuan Wang (Archives of Medical Science)
Introduction Iodine deficiency is a global issue; however, no comparable assessments of the burden of iodine deficiency have been conducted worldwide. Hence, we measured the estimated annual percentage changes (EAPCs) from 1990 to 2019. Our aim was to quantify the geographic differences in the burden of iodine deficiency worldwide.